FLOATING DRUG DELIVERY SYSTEM: AN OUTLOOK - Choudhury, Ananta; Renthlei, Lalmalsawmi; Dewan, Manjima; Ahmed, Raju; Barakoti, Himal; Dey, Biplab Kumar (Journal of Applied Pharmaceutical Research, 2019)
Floating drug delivery is considered as the most effective amongst the several approaches of gastro retentive drug delivery systems. The short gastric residence times (GRT) and unpredictable gastric emptying times (GET) are the two most important parameters that play a vital role in improving the bioavailability of drugs those are having an absorption window at the stomach. The floating drug delivery approach is a low-density system that may be effervescent or Non-Effervescent type with sufficient buoyancy to flow over the gastric contents and remain buoyant in the stomach without affecting the stomachic emptying rate for a prolonged duration. Floating dosage forms include tablets, granules, capsules, microspheres, microparticle, etc. are few formulations available commercially. A comprehensive summary of different floating drug delivery and its present status has been highlighted in this review.